1985
DOI: 10.1039/c39850000737
|View full text |Cite
|
Sign up to set email alerts
|

Chiral bicycles from ribonolactone

Abstract: The preparation of the chiral butenolide (4b) is described, together with its use in annulation reactions yielding stereochemically defined bicyclo[4.3.0], [3.3.0], and [3.1 .O] ring systems; the synthetic utility of these species is indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…11 We were interested in comparing their results with our own. Formerly, we had prepared the benzyloxymethylfuranone 1 by reaction of the parent alcohol 13 (readily available from Dmanitol) 12 with benzyl bromide and silver(I) oxide, but we have now improved the benzylation efficiency by the use of benzyltrichloroacetimidate in dichloromethane in the presence of trifluoromethanesulfonic acid. 13 Under these new conditions, furanone 1 was isolated in 93% yield (Scheme 3).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…11 We were interested in comparing their results with our own. Formerly, we had prepared the benzyloxymethylfuranone 1 by reaction of the parent alcohol 13 (readily available from Dmanitol) 12 with benzyl bromide and silver(I) oxide, but we have now improved the benzylation efficiency by the use of benzyltrichloroacetimidate in dichloromethane in the presence of trifluoromethanesulfonic acid. 13 Under these new conditions, furanone 1 was isolated in 93% yield (Scheme 3).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…To the best of our knowledge, the first mention of Diels-Alder reaction on protected HBO has been reported by Mann and Thomas with the simplest possible diene, butadiene. 35 Only one product, 21 (Chart 1) has been observed in 75% yield after one week of reaction. While Mann and Thomas have performed a Lewis acid-mediated Diels-Alder reaction, one year later, Ortuno et al reported on thermal Diels-Alder reactions on various chiral butenolides (Table 2, entries 1-5).…”
Section: Diels-alder Reactionsmentioning
confidence: 98%
“…1,3-dipolar cycloaddition is a [3+2] cycloaddition between a dipole, such as nitrones or diazo compounds, and a dipolarophile, HBO and derivatives in this review. Interest for the mechanism and selectivity of 1,3-dipolar cycloadditions on HBO began in the mid-90's, even if the first attempt was reported in 1985, 35 this reaction being used regularly thereafter in total syntheses. 47,48 Baskaran and co-workers performed 1,3-dipolar cycloadditions of diazomethane 49 and nitrones 50,51 on α,β-unsaturated esters and lactones.…”
Section: Studies Of 13-dipolar Cycloadditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…[6b] Ascorbic acid analogues [7] have been used as key intermediates in the synthesis of (ϩ)-and (Ϫ)-eldanolide, [8] the antileukaemic lignans (ϩ)-trans-burseran, [9] (Ϫ)-isostegane, [9] (ϩ)-and (Ϫ)-steganacin, [10] (Ϫ)-verrucarinolactone, [11] and chrysanthemic acid analogues. [12] Although a number of syntheses of γ-lactones and butenolides are known, [13] they are in many cases limited to specific substitution patterns. The development of alternative strategies for the preparation of these important heterocycles is therefore of considerable importance.…”
Section: Introductionmentioning
confidence: 99%